PENGARUH EXPERIENTAL MARKETING TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Muhammad Fahruzi; Saida Zainurossalamia; Sri Wahyuni (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Muhammad Fahruzi, 2019 Effect of Experiental Marketing on Consumer Loyalty with Consumer Satisfaction as an Intervening Variable (Study in Midtown Hotel Samarinda), guided by Advisor I, Mrs. Dr. Saida Zainnurossalamia, S.E., M.Si and Ms. Dr. Hj. Sri Wahyuni, S.E., M.Si as Advisor II.          This study analyzed using a sample of 110 respondents or hotel guests who were visiting and staying at the hotel more than twice, using the purposive sampling method. The purpose of this study was to find out how the direct and indirect effects of the Experiential Marketing indicators consisting of sense, feel, think, act, relate to Consumer Loyalty were intervened by Consumer Satisfaction in Midtown Samarinda hotels. The data analysis technique used was the path analysis method ( path analysis).          The results of the study show that Marketing Experiences have a positive and insignificant effect on Consumer Loyalty, in Intervening by Consumer Satisfaction significant positive effect on Consumer Loyalty.